Women and genocide: survivors, victims, perpetrators - Bemporad, Elissa; Warren, Joyce W. (Indiana University Press, 2018)
The genocides of modern history–Rwanda, Armenia, Guatemala, the Holocaust, and countless others–and their effects have been well documented, but how do the experiences of female victims and perpetrators differ from those of men? In Women and Genocide, human rights advocates and scholars come together to argue that the memory of trauma is gendered and that women's voices and perspectives are key to our understanding of the dynamics that emerge in the context of genocidal violence. The contributors of this volume examine how women consistently are targets for the sexualized violence that serves as an instrument of ethnic cleansing, how female perpetrators take advantage of the new power structures, and how women are involved in the struggle for justice in post-genocidal contexts. By placing women at center stage, Women and Genocide helps us to better understand the nexus existing between misogyny and violence in societies where genocide erupts.